Implementasi Kurikulum Pendidikan Anti Korupsi Di STIB Banyuwangi sebagai Upaya Preventif Anti Korupsi - Juwono, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2021)
One of the organizers of Anti-Corruption Education in the curriculum of higher education in East Java Banyuwangi regency is the Islamic High School Blambangan Banyuwangi (STIB). This effort is expected to break the chain of corruption in the future. Students after obtaining Anti-Corruption Education have a full awareness of how corruption is very unappreciative and very detrimental to the State. This awareness fosters a concrete reaction from students to participate in the prevention of corruption by committing to protect themselves and their families from being involved in corruption. Student efforts in the prevention of corruption are also seen in their responsiveness overseeing the misuse of positions and operational state funds for development.